An Ontology for Strongly Sustainable Business Models: Defining an Enterprise Framework Compatible With Natural and Social Science. (March 2016) - Upward, Antony; Jones, Peter
Business is increasingly employing sustainability practices, aiming to improve environmental and social responsibility while maintaining and improving profitability. For many organizations, profit-oriented business models are a major constraint impeding progress in sustainability. A formally defined ontology, a model definition, for profit-oriented business models has been employed globally for several years. However, no equivalent ontology is available in research or practice that enables the description of strongly sustainable business models, as validated by ecological economics and derived from natural, social, and system sciences. We present a framework of strongly sustainable business model propositions and principles as findings from a transdisciplinary review of the literature. A comparative analysis was performed between the framework and the Osterwalder profit-oriented ontology for business models. We introduce an ontology that enables the description of successful strongly sustainable business models that resolves weaknesses and includes functionally necessary relationships.